Pelatihan Penggunaan Media Flash Card dalam Pembelajaran Bahasa Inggris pada Taman Belajar Ar Raihan - Ramadhianti, Agustina; Somba, Sugianti; Rosyada, Amrina (Universitas Nusantara PGRI Kediri, 2023)
Education is necessary for every individual so education at an early age is a prominent stage. At this level, various educational settings from informal, non-formal, or formal institutions as well are available. One of the non-formal institutions for early-stage education is Taman Belajar Ar Raihan. This institution helps students to gain knowledge in several skills, including in the academic field. One of the academic subjects is English for the Kindergarten level. Based on the concept of learning with fun, a variety of learning approaches and media are needed to promote a more interesting and fun learning classroom. By focusing on the use of the flash card as the learning media, the team provided training on the use of the flash card in improving English vocabulary mastery in particular. In this way, the students are more interested and happier to learn English.